THE ARCTIC FUND: OPPORTUNITIES FOR ENHANCING TAX INCOME GENERATION - Roman R. Nogovitsyn; Tatiana S. Sofronova; Alexey V. Novikov (Север и рынок: формирование экономического порядка, 2023)
This study was conducted in order to develop methodological approaches to the generation of financial resources for the Arctic Zone Development Fund of the Russian Federation (Arctic Fund). The object of the study is the Arctic Fund, established by the Government of the Russian Federation in December 2022. The sources of funding are the subject of the study. The relevance of this research stems from the unique characteristics of the Arctic territories, where the financial base for development relies on the social and environmental responsibility of major taxpayers. The study builds upon data from the Federal Tax Service, the Federal Treasury, the Federal Agency for Mineral Resources, and the Torgi federal information system covering the period from 2011 to 2021.